Ending Violence in Schools : An Investment Case - Wodon, Quentin; Fèvre, Chloe; Malé, Chata; Nayihouba, Ada; Nguyen, Hoa (World Bank, Washington, DC, 2021)
While there is no doubt that education is transformative, simply going to school is not enough. Real learning, the process of receiving and distilling information, of thinking and creating and producing and socializing, is less likely to happen if a child is scared or traumatized. Preventing violence in and through school is therefore a prerequisite for girls and boys getting the education they need and deserve, and acquiring the skills, knowledge and values that provide the foundations for strong and inclusive societies. This report demonstrates that violence in and around schools negatively impacts educational outcomes, and society pays a heavy price as a result (with an estimate of $11 trillion in lost lifetime earnings). Cost-benefit analyses suggest that implementing interventions to prevent violence in and through schools from early childhood to secondary education is a smart economic investment. Rigorously evaluated programs and policies aimed at preventing violence at different levels of the education system show that action is feasible. The benefits of investing in preventing violence in and through schools is likely to far outweigh the costs.